A Study on the effect of marketing using virtual mirror technology on customer satisfaction - JO, Junghee (KDI School, 2021)
This study is to research how high-tech technologies provided by customers in offline and online businesses affect customer behavior in the 4th industrial revolution environment. In the purpose of this study is to study how virtual mirror technology, which is a virtual reality technology, affects customers'' expectation satisfaction and intention to use that rarely examined in previous studies. In this study, a research model was established based on sensory marketing theory. That is, based on the Stimulus, Organism, Response (S-O-R) model, the independent variable was set as the sensory stimulus of virtual reality technology and the emotional response according to the stimulus of the virtual reality technology, and the dependent variable was set as the behavioral response according to the sensory stimulus and emotional response. Specifically, the independent variables were the sensory stimulation and emotional response of virtual reality technology, and the user''s pleasure, perceived product quality, remote reality, interaction, and immersion were set. As the dependent variable, the user''s expected satisfaction and intention to use were set as behavioral responses. Based on this research model, a research hypothesis was established. In order to verify the research hypothesis established based on the research model, empirical research analysis was conducted. The subjects of the study were random sampling, which is a non-probability sampling method, and the subjects were easily accessible by the researcher and those who had experience in shopping malls were selected. 117 questionnaire results were collected for those who experienced online and offline shopping malls. The collected data were analyzed using IBM SPSS statistics 22.0. As an analysis technique, frequency analysis is performed to organize general characteristic samples, reliability analysis is performed to test the reliability of each variable, and factor analysis is performed to verify the construct validity of each variable, and regression analysis was performed to find out the influence between the variables using the representative values of each variable that secured reliability and validity. Through this, we analyzed how virtual reality technology affects customer behavior. The analysis results of this study are as follows. First, as a result of analyzing the effect of sensory stimulation and emotional response of virtual reality technology on expected satisfaction, it was found that there was a positive influence in the order of i) immersion, ii) remote reality, and iii) sensory stimulation. Second, as a result of analyzing the effects of sensory stimulation and emotional response of virtual reality technology on intention to use, it was found that there was a positive influence in the order of i) pleasure, ii) immersion, and iii) product quality. Third, as a result of analyzing the effect of virtual reality technology''s expected satisfaction on intention to use, it was found to have a (+) influence. Fourth, the independent variable that has a (+) effect on both the user''s expectation satisfaction and intention to use is the user''s emotional response variable, which is the degree of commitment. In other words, the degree of immersion affects the user''s expected satisfaction and intention to use. Fifth, the independent variable that does not have a positive effect on both user''s expectation satisfaction and intention to use is interaction as a user''s emotional response variable. That is, interaction does not have a positive effect on expectation satisfaction and intention to use. Considering the results of this analysis, the implications from a business management perspective are as follows. First, when using virtual reality technology, managers should continuously seek ways to increase customer satisfaction by stimulating the senses of buyers and improving the sense of remote reality and immersion. Second, the CEO should devise a way to induce customers'' interest, improve immersion through pleasure, and increase the intention to use the product by improving product quality. Third, empirical analysis showed that interaction did not affect expected satisfaction and intention to use. Virtual reality technology is used as a device to explain products in detail, and subscription inducement or mileage is used to improve access to shopping malls. It needs to be used side by side. The results of this study provides how to foster better relationship with customers by applying advanced technologies. In particular, adoption of technologies will help customers’ decision making processes both via online and offline and enhance satisfaction and loyalty that are critical aspects for Customer Relationship Management (CRM).
Thesis(Master) -- KDI School: Master of Public Management, 2021
Keywords: Marketing; Consumer satisfaction